Recognition Discriminability and Response Bias in the Shiraz Verbal Learning Test Among Older People With Amnestic Mild Cognitive Impairment, Alzheimer\'s Disease, and Memory Normal - Fahimeh Rahmani; Roya Marsa; Mohammad Saeed Khanjani; Soraya Marsa; Kourosh Shahrivar (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Most studies have investigated the effect of pathological aging brain on information recall and recognition memory of patients by using yes-no procedures. For this reason, they provide an incomplete picture of memory defect, and other factors related to recognition memory such as recognition discriminability (RD) and response bias (RB) are not taken into consideration. In this regard, present study aims to examine the effect of amnestic mild cognitive impairment (MCI) and Alzheimer's disease on RD and RB using the Shiraz verbal learning test (SVLT) compared to healthy peers. Methods & Materials This descriptive cross-sectional study was conducted on 190 eligible older people aged 60-89 years with amnestic MCI, Alzheimer's disease, and normal memory in Shiraz, Iran, in 2021. The data collection tools were SVLT and mini-mental status examination. Data analysis was done in SPSS software, version 19 using descriptive statistics (No., Mean±SD) and analytical tests (ANOVA and Scheffe's test). The significance level was set at 0.05. Results The patients with amnestic MCI and Alzheimer's disease had significantly lower scores than the healthy older people in recognition memory performance (P<0.001). They also had lower scores and more false-positive errors in RD domains (global, semantic, source, and new) (P<0.001). in RB, the patients with Alzheimer's disease had significantly higher scores than older people with amnestic MCI and normal memory (P<0.001).    Conclusion The study of recognition memory performance (RB and RD) in patients with amnestic MCI can provide useful information to predict Alzheimer's disease in the prodromal stage.